Numerical groundwater flow modeling applied to dewatering prediction of Cauê Aquifer in Alegria Mine, east of quadrilátero ferrífero, Minas Gerais - Chiste-Costa, João Paulo (2017)
The feasibility to achieve a water table drawdown is one of realities of Quadrilátero Ferrífero District. In general, iron ore reserves are located in Cauê Formation, same geological unit of main aquifer of the region, that increasing complexity to acess ore reserve below piezometric level. Alegria Mine, located in east of Quadrilátero Ferrífero, is an example of a mining operation that, in order to be deepened, will need to be dewatering, which should occur gradually over the years. This study has the objective to perform conceptual and numerical groundwater flow models to simulate flow rate and number of pumping wells to achieve the drawdown necessary to acess the ore reserve, according an hyphotetical Samarco\'s mine planning schedule. Simulated model indicates that 98 pumping wells should be installed to access the ore reserve, which will be distributed in Alegria North, Alegria Center and Alegria South. The peak flow will be in order of 11,400 m³/h. It was also simulated the efficiency of cut-off walls system in reducing leakage from Piracicaba River flow-rate to aquifer, under an extensive cone of depression. Eventual reduction of base-flow was calculated in the model that allowed planning the flow-rate to be returned to Piracicaba River and tributaries in order to preserve historical flows. The proposed structures for dewatering program will be jointly evaluated in the hydrogeological model in order to maintain sustainability of project with minimum environmental impact of the Piracicaba river.